FORMATION OF ECOLOGICAL CULTURE OF STUDENTS IN TEACHING CHEMISTRY - Grabovyy, Andrii K. (Educological discourse, 2015)
The study examined the theoretical and methodological principles of formation of ecological culture of the students while studying chemistry in secondary schools. Theoretical analysis of the literature on the research showed that the problem of formation of ecological culture of the students while studying chemistry at school is important, but understudied. In summary, the meaning of the concept of «ecological culture» like to use the ability of people to their environmental knowledge and skills in practice. Components is environmental culture knowledge, values, experience activities. Ecological culture pupils formed in the study ecological school chemistry: environmental component content of basic chemistry course, ecological chemical experiment, ecological task problem.